2008
DOI: 10.1111/j.1469-8749.2007.02017.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient magnetic resonance diffusion abnormalities in West syndrome: the radiological expression of non‐convulsive status epilepticus?

Abstract: The purpose of this study was to report patients with pharmacoresistant West syndrome of unknown cause whose magnetic resonance imaging (MRI) with diffusion weighted imaging (DWI) showed a transient decrease of diffusion in subcortical structures. Of 20 patients investigated over a 2-year period, three males and three females constitute the present series. They had daily clusters of infantile spasms with hypsarrhythmia for 4 to 24 months before the first investigation. Four were severely hypotonic. All aetiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
6
18
1
Order By: Relevance
“…These studies (Desguerre et al, 2008;Pearl et al, 2009) have challenged the conclusion that vigabatrin does The purpose of this study was to expand on the knowledge previously published on the central nervous system effects of Vigabatrin in juvenile animals. By employing extended sectioning of the brain and by using four different tissue staining techniques it is demonstrated that oral administration of Vigabatrin to juvenile rats (treatment periods of post-natal day (PND) 4-7, 7-14 or 14-30) will cause histological CNS changes at dose levels of 15 and 50 mg/kg/day, but not at a dose level of 5 mg/kg/day.…”
Section: Introductionmentioning
confidence: 99%
“…These studies (Desguerre et al, 2008;Pearl et al, 2009) have challenged the conclusion that vigabatrin does The purpose of this study was to expand on the knowledge previously published on the central nervous system effects of Vigabatrin in juvenile animals. By employing extended sectioning of the brain and by using four different tissue staining techniques it is demonstrated that oral administration of Vigabatrin to juvenile rats (treatment periods of post-natal day (PND) 4-7, 7-14 or 14-30) will cause histological CNS changes at dose levels of 15 and 50 mg/kg/day, but not at a dose level of 5 mg/kg/day.…”
Section: Introductionmentioning
confidence: 99%
“…Reversal of findings is seen with cessation of vigabatrin and even while taking the drug [6,12,13,17]. If vigabatrin is discontinued, reversal of neuroimaging abnormalities occurs only after a certain period of time has elapsed which is thought to be greater than 3 months [6].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in some publications of series of patients, even recognizing the presence of a mitochondrial disease, authors viewed the signal changes as a direct consequence of seizures [1,5,8]. In 1 report of 6 infants with infantile spasms and subcortical gray matter restriction of diffusion, authors consider the SIE as the main hypothesis to explain the cytotoxic edema [9]. Later, it was realized that vigabatrin could lead to this MRI pattern [10].…”
Section: Discussionmentioning
confidence: 99%